2015
DOI: 10.1186/s12284-015-0045-6
|View full text |Cite
|
Sign up to set email alerts
|

Abiotic stress and genome dynamics: specific genes and transposable elements response to iron excess in rice

Abstract: BackgroundIron toxicity is a root related abiotic stress, occurring frequently in flooded soils. It can affect the yield of rice in lowland production systems. This toxicity is associated with high concentrations of reduced iron (Fe2+) in the soil solution. Although the first interface of the element is in the roots, the consequences of an excessive uptake can be observed in several rice tissues. In an original attempt to find both genes and transposable elements involved in the response to an iron toxicity st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
82
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(93 citation statements)
references
References 107 publications
(134 reference statements)
5
82
0
1
Order By: Relevance
“…However, it was proved for many plant species that the tendency of TE to insert into repetitive DNA mitigates their deleterious potential (SanMiguel et al 1996;Kalendar et al 1999;Suoniemi et al 1997;Ramsay et al 1999). Furthermore, it was observed that a rapid mutational process in plants caused by TE during environmental stress, could be adventitious for the particular group of organisms, by rapidly increasing genotypic variability, which may be associated with adaptation for abiotic stress (Wessler 1996;Kalendar et al 2000;Finatto et al 2015). The development of iPBS technique allowed for tracking genomic changes induced by TE in species for which genomic information is limited: Prunus arme− niaca (Baránek et al 2012), Malus x domestica (Kuras et al 2013), Cicer species (Andeden et al 2013), Psidium guajava (Mehmood et al 2013), Myrica rubra (Chen and Liu 2014).…”
Section: Discussionmentioning
confidence: 99%
“…However, it was proved for many plant species that the tendency of TE to insert into repetitive DNA mitigates their deleterious potential (SanMiguel et al 1996;Kalendar et al 1999;Suoniemi et al 1997;Ramsay et al 1999). Furthermore, it was observed that a rapid mutational process in plants caused by TE during environmental stress, could be adventitious for the particular group of organisms, by rapidly increasing genotypic variability, which may be associated with adaptation for abiotic stress (Wessler 1996;Kalendar et al 2000;Finatto et al 2015). The development of iPBS technique allowed for tracking genomic changes induced by TE in species for which genomic information is limited: Prunus arme− niaca (Baránek et al 2012), Malus x domestica (Kuras et al 2013), Cicer species (Andeden et al 2013), Psidium guajava (Mehmood et al 2013), Myrica rubra (Chen and Liu 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This is the third report linking WRKYs with iron excess response (Ricachenevsky et al, 2010;Finatto et al, 2015). The first shows that OsWRKY80, which is also involved in rice drought response and senescence, increases its transcriptional expression (3-fold) after 6 DUS at 500 ppm (Ricachenevsky et al, 2010).…”
Section: Discussionmentioning
confidence: 76%
“…The first shows that OsWRKY80, which is also involved in rice drought response and senescence, increases its transcriptional expression (3-fold) after 6 DUS at 500 ppm (Ricachenevsky et al, 2010). The second is a microarray analysis showing that 19 WRKYs are up-regulated when rice is under iron excess (7 mM for 18 DUS), suggesting that this family can perform an important role in iron homeostasis (Finatto et al, 2015).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations